How the approval of rules influences motivation. Issue 1 (2014) - ,
Abstract : Purpose – With their specific characteristics, religious orders provide an interesting environment that can be used to deepen the understanding and dynamics of work motivation in the public sector. The paper aims to discuss this issue.Design/methodology/approach – The paper empirically investigates the levels and kinds of motivation (from extrinsic to intrinsic) in different religious orders, and analyze some major factors of influence. A broad survey of monastic leaders offers a unique data set to analyze the influence of constitutions and traditions on motivation in a quantitative and comparative way. The theoretical foundations are based upon self‐determination theory (SDT), formalization and public service motivation.Findings – The paper shows that even the most constrained and hierarchically structured communities succeed in preventing a crowding out of self‐determined motivation. On the one hand, this can be ascribed to the influence of faith and religion. On the other hand, and this is the focus of the paper, the analysis suggests that if norms and structures are approved and considered essential, a crowding‐out effect is absent, and motivation levels can be maintained.Research limitations/implications – This study has an explorative character; it is intended to provide interest for further research. Because of the particular position of religious orders, and equally because of the relatively small sample and few variables concerning the approval of rules and traditions, further investigations in other settings are needed.Practical implications – An alternative path to increase public service motivation comes into play. The negative effects of little or no autonomy and strict regulation in an organization's daily routines can be tempered by a conscious composition and awareness of governance, i.e. an understanding of and agreement upon constitutions, rules and traditions.Originality/value – The approval of constitutions and traditions has received little study, yet offers new insights into public service motivation, SDT and formalization. Acknowledgements : The author extends special gratitude to the Swiss National Foundation for their financial engagement. The author's work would not have been possible without the commitment of many padres, brothers, sisters and employees of the religious orders.